Modeling performance of different sustainable self-compacting concrete pavement types utilizing various sample geometries - Saadoon Tahseen D.; Obaidi Hadel; Dulaimi Anmar; Ghiassi Bahman (Open Engineering)
Concrete is most used material in the building and transportation projects. The crucial and essential characteristic of the concrete is its compressive performance. The current plan is to investigate and predict how geometries of specimen affected the mechanical performance of environmentally friendly self-compacting normal-strength concrete (NSC) and high-strength concrete (HSC) containing recycled concrete as partial replacement of virgin (not recycled) aggregate, and using of pozzolanic material (fly ash) as replacement of cement. More than 100 samples of standard and HSC compositions, both cylindrical and cubic/prismatic, were cast and tested. The experimental results indicate that the replacement of virgin aggregate lead to the reduced mechanical performance of the concrete. The replacement of fine aggerate has less negative effect on strength than coarse aggregate. Although a reduction in strength was observed, the 60% replacement level still achieved strength values that are acceptable according to the standards of the pavement sector. The measured compressive strength of NSC and HSC is influenced by specimen size, slenderness ratio (H/D: height/diameter or smaller dimension), and shape. When cylinders and prisms are compared at the same H/D values, the compressive strength values for prism specimens are higher. For the same specimen shape, the effect of slenderness ratio increases with specimen size. The type of concrete (NSC or HSC) does not clearly affect the differences in strength between the types of tested specimens. The model prediction of the mechanical performance of various shapes and sizes of NSC and HSC based on small sample sizes obtained a confidence factor greater than 0.9, supporting the use in other works or research.